IMPLEMENTASI METODE DOUBLE EXPONENTIAL SMOOTHING PADA PREDIKSI JUMLAH PRODUK UMKM - Dorestin, Nacita Agnes; Vulandari, Retno Tri; Saptomo, Wawan Laksito Yuly; Widada, Bebas; Wijayanto, Hendro (Journal of Technology, Mathematics and Social Science, 2023)
Y2K Batik is an SME (Small and Medium Enterprise) engaged in batik. Y2K Batik produces and sells beach wear with various motifs. One of the important things in business is inventory of merchandise, inventory of merchandise is a factor in determining the success of a trading company to achieve its goals, because the goods sold affect the level of income to increase company profits. With these considerations, it is necessary to analyze the production of beach wear for the availability of merchandise in fulfilling customer orders. Based on the above background, the scope of the problem in this study is master data collection obtained from records of selling beach batik cloth periodically from time to time. By utilizing the existing data and applying certain methods, a sales forecasting prediction can be made using the Double exponential Smoothing method. From the results of calculations and testing of forecasting data on the Mandala Motif Beach Fabric variable with the most optimal value using = 0.9 of 2127 with an error value of 19.46% and an accuracy rate of 80.54% (Good). The Canting Motif Beach Wear variable with the most optimal value using = 0.9 of 3174 with an error value of 3.61% and an accuracy rate of 96.39% (Very Good). Double Exponential Smoothing is the most widely used method to determine the trend equation of the second smoothing data through a smoothing process. The programming language uses Microsoft Visual Studio 2013 and the DBMS uses Microsoft SQL Server 2012. The purpose of this research is to create a system that can simplify the process of analyzing the production of beach wear in order to meet the availability of goods ordered by customers